Application of the CEFR Concept in Arabic Language Learning in Madrasah Aliyah eL-Bas (Bina Anak Sholeh Institute) Ciamis - Desy Maulani Rizki; Rosnaeni (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2022)
This study aims to determine the CEFR-based assessment carried out in Arabic language learning at MA eL-Bas Ciamis. This research uses qualitative methods with data collection techniques using observation, interviews, and documentation. The results obtained from this study show that CEFR-based assessment in Arabic language learning at MA El-Bas Ciamis is used to determine students' Arabic proficiency and makes teachers simple in carrying out the assessment process for students. Teachers are facilitated in evaluating Arabic learning at the end of education.